2018
DOI: 10.1002/psc.3095
|View full text |Cite
|
Sign up to set email alerts
|

Human apolipoprotein E as a reservoir of cryptic bioactive peptides: The case of ApoE 133‐167

Abstract: Bioactive peptides derived from the receptor-binding region of human apolipoprotein E have previously been reported. All these peptides, encompassing fragments of this region or designed on the basis of short repeated cationic sequences identified in the same region, show toxic activities against a broad spectrum of bacteria and interesting immunomodulatory effects. However, the ability of these molecules to exert antibiofilm properties has not been described so far. In the present work, we report the characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…Research in the field of lipoproteins has the potential to discover new host defense molecules and the mechanisms by which they participate in the immune response to infection ( 12 , 13 , 23 , 32 ). Several in vitro studies have shown that prototypic peptides with the sequence corresponding to the apoE receptor-binding region have strong antimicrobial activity ( 15 , 16 , 17 , 19 , 33 ). In addition, in vivo studies have revealed that apoE is a protein with anti-inflammatory ( 34 , 35 , 36 , 37 ) and anti-infective properties, showing that apoE-deficient mice exhibited an increased susceptibility in response to Gram-negative or fungal infection ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research in the field of lipoproteins has the potential to discover new host defense molecules and the mechanisms by which they participate in the immune response to infection ( 12 , 13 , 23 , 32 ). Several in vitro studies have shown that prototypic peptides with the sequence corresponding to the apoE receptor-binding region have strong antimicrobial activity ( 15 , 16 , 17 , 19 , 33 ). In addition, in vivo studies have revealed that apoE is a protein with anti-inflammatory ( 34 , 35 , 36 , 37 ) and anti-infective properties, showing that apoE-deficient mice exhibited an increased susceptibility in response to Gram-negative or fungal infection ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, various peptides from the receptor-binding region of apoE (amino acid residues 130–150), which is essential for its biological function in lipid metabolism, have been shown to exert both antiviral and antibacterial activity ( 14 , 15 , 16 , 17 ). This region is responsible for the binding of apoE to the LDL receptor family, and also, within this sequence, residues 142–147 (the heparin-binding domain) mediate attachment of apoE to cell surfaces ( 18 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, computational approaches combining characteristic features of length, charge, and hydrophobicity has led to discovery of protein subdomains which could have the same functions as natural cationic HDPs [ 41 , 42 , 43 ]. For example, a region in the poorly characterized human protein 11-beta-hydroxysteroid dehydrogenase type 3 (HSD 3) showed many HDP-like characteristics, including anti-biofilm and LPS-neutralizing effects [ 42 ].…”
Section: Structural Aspectsmentioning
confidence: 99%
“…Here, we analyze for the first time the antimicrobial and anti-biofilm properties of two recently characterized AMPs [33] towards Pseudomonas and Burkholderia strains clinically isolated from CF patients. AMPs under test have been identified in human apolipoprotein B (ApoB) by using a bioinformatic method developed by our research group [33][34][35][36][37][38][39][40][41]. Indeed, it is increasingly evident that eukaryotic proteins, with functions not necessarily related to host defense, act as sources of "cryptic" bioactive peptides released upon proteolytic processing by bacterial and/or host proteases [42][43][44].…”
Section: Introductionmentioning
confidence: 99%